Relevance in argumentation - Walton, Douglas N. (Mahwah, N.J. : L. Erlbaum Associates, 2004)
"This volume is intended for graduate and advanced undergraduate courses in field using argumentation theory - law (in particular, evidence law), artificial intelligence (especially multi-agent computing), linguistics, cognitive science, and speech communication, in addition to philosophy. The work also has practical use, as it applies theory directly to familiar examples of argumentation in daily and professional life. With a clear and comprehensive method for determining relevance and irrelevance, it can be convincingly applied to practical problems about relevance, including those in legal and political argumentation."--BOOK JACKET.
Includes bibliographical references (p. [289]-297 ) and indexes.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Relevance (Philosophy); Logic; Electronic books